Laparoscopic Lavage Is Feasible and Safe for the Treatment of Perforated Diverticulitis With Purulent Peritonitis: The First Results From the Randomized Controlled Trial DILALA. Issue 1 (January 2016) - Angenete, Eva; Thornell, Anders; Burcharth, Jakob; Pommergaard, Hans-Christian; Skullman, Stefan; Bisgaard, Thue; Jess, Per; Läckberg, Zoltan; Matthiessen, Peter; Heath, Jane; Rosenberg, Jacob; Haglind, Eva
Abstract : Objective: To evaluate short-term outcomes of a new treatment for perforated diverticulitis with purulent peritonitis in a randomized controlled trial. Background: Perforated diverticulitis with purulent peritonitis (Hinchey III) has traditionally been treated with surgery including colon resection and stoma (Hartmann procedure) with considerable postoperative morbidity and mortality. Laparoscopic lavage has been suggested as a less invasive surgical treatment. Methods: Laparoscopic lavage was compared with colon resection and stoma in a randomized controlled multicenter trial, DILALA (ISRCTN82208287). Initial diagnostic laparoscopy showing Hinchey III was followed by randomization. Clinical data was collected up to 12 weeks postoperatively. Results: Eighty-three patients were randomized, out of whom 39 patients in laparoscopic lavage and 36 patients in the Hartmann procedure groups were available for analysis. Morbidity and mortality after laparoscopic lavage did not differ when compared with the Hartmann procedure. Laparoscopic lavage resulted in shorter operating time, shorter time in the recovery unit, and shorter hospital stay. Conclusions: In this trial, laparoscopic lavage as treatment for patients with perforated diverticulitis Hinchey III was feasible and safe in the short-term.